Investigation of the Ga-Sb-S chalcogenide glass with low thermo-optic coefficient as an acousto-optic material. Issue 15 (1st August 2022) - Xu, Zenghua; Dai, Shixun; Liu, Chengcheng; Wu, Zhongchao; Xu, Lulu
Abstract: In this study, two series of Gax Sb40-x S60 (x = 4, 6, 8, 10 mol%) and Gay Sb36 S64-y (y = 3, 5, 6 mol%) glasses were prepared and the relationship between their compositional and acousto-optic (AO) properties was investigated systematically for the first time. In the Gay Sb36 S64-y system, the AO figure of merit ( M 2 ) increased as the Ga increased, and the maximum M 2 of the Ga6 Sb36 S58 glass was 455.78 × 10 −18 s 3 /g, which is ∼301 times greater than that of fused silica and ∼2.5 times greater than that of As2 S3 chalcogenide (ChG) glass at 1550 nm. However, its thermo-optic coefficients (d n /d T ) varied greatly (32.1 × 10 −6 °C −1 –57.2 × 10 −6 °C −1 ), and acoustic attenuations ( α ) at 10 MHz were high, from 5.446 dB/cm to 7.274 dB/cm. In the Gax Sb40-x S60 glass system, the M 2 value and α at different ultrasonic frequencies gradually decreased with the improvement of Ga. Compared with the Gay Sb36 S64-y system, the Gax Sb40-x S60 glass system had lower α (at 10 MHz) and d n /d T, which are 5.001 dB/cm–5.563 dB/cm and 17.3 × 10 −6 °C −1 –55.6 × 10 −6 °C −1, respectively. These results provide a significant reference for the further development of novel ChG glasses and help expand their application fields.